An Analysis of Persuasive Strategies Used in Slogan Woman Cosmetic Products SAFI Advertisement on Instagram - Rita Harisma; Erlindawaty Erlindawaty; Rahmanita Agustina (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
This research investigates about the persuasive strategies used in slogan woman cosmetic products Safi advertisement on Instagram. Making use of slogan in advertisement has increased so considerably that a large proportion of todays advertisements. The objectives of this research to find out the type of persuasive strategies and the way to persuade consumers used in slogan advertisement of Safi cosmetic products. This research used qualitative method. The researcher uses Keraf (2007:124) theory about the types of persuasive strategies and Aristotle (1954) theory about the way to persuade consumers. In this research, the researcher used 22 data of slogan advertisement from Safi official account on Instagram. Based on the data analysis, the researcher found that there are five types of persuasive strategies used in this research, they are rationalization (9 data), identification (4 data), suggestion (5 data), conformity (11 data) and compensation (8 data). And the way to persuade consumers, they are: ethos (11 data), pathos (2 data) and logos (9 data). Persuasive strategies must be used in slogan woman cosmetic products because the persuasive strategies have a meaning to influence the mind, manner or opinion of someone with some reason and evidence.